Selection Of Shipping Services Using Analytical Hierarchy Process (AHP) Method - Dzakiyah Agustin Puspitasari; Febriola Rania Trihelmina; Maya Kencana Wulandari; Anindiatie Parastikasari; Hidayatul Khusna (Department of Statistics ITS, 2021)
Online business has come along way since these early days, where people can purchase items from the comfort of their own homes and work place. This causes people to choose to shop online rather than go to offline store, thus, the freqeuncy of delivery services keep getting higher day by day. In determining the right shipping service, every people has a different needs. This study aims to identify factors that affect customers in choosing shipping services. The variable includes three dimension which are alternative, criteria, and sub-criteria. The number of respondents for this study is 72. Four major shipping service companies in Indonesia were selected to be the alternative includes JNE, J&T, SiCepat and Pos Indonesia. The analysis shows that there are 5 criteria and 2 sub criteria for each criteria, that can be used to measure user preference of choosing shipping services. In this study it was found that the value of consistency ratio in each matrix paired is  0,1 so that the AHP method inthis study has optimal results. From the analysis, each criterion was weighted to rank the customers preference of choosing a shipping services relatively of each other. The best delivery service selected is J&T with The criteria sorted from most important to least important are security, quality of service, price, area coverage and distance.